Current and Emerging Therapeutics for Cutaneous T-Cell Lymphoma: Histone Deacetylase Inhibitors. (16th August 2012) - Rodd, Annabelle L.; Ververis, Katherine; Karagiannis, Tom C.
Abstract : Cutaneous T-cell lymphoma is a term that encompasses a spectrum of non-Hodgkin's T-cell lymphomas with primary manifestations in the skin. It describes a heterogeneous group of neoplasms that are characterised by an accumulation of malignant T cells of the CD4 phenotype that have the propensity to home and accumulate in the skin, lymph nodes, and peripheral blood. The two most common variants of cutaneous T-cell lymphoma include mycosis fungoides and the leukemic variant, the Sézary syndrome. While numerous treatments are available for cutaneous T-cell lymphoma and have shown to have success in those with patch and plaque lesions, for those patients with tumour stage or lymph node involvement there is a significant decline in response. The relatively new therapeutic option with the use of histone deacetylase inhibitors is being advanced in the hope of decreasing morbidity and mortality associated with the disease. Histone deacetylase inhibitors have been shown to induce changes in gene expression, affecting cell cycle regulation, differentiation, and apoptosis. The aim of this paper is to discuss CTCL in the context of advances in CTCL treatment, specifically with HDAC inhibitors.